2019
DOI: 10.17529/jre.v15i2.13546
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Aspek Kecepatan dan Ketepatan pada Sun Tracker Dua Sumbu Berbasis Sensor Berbentuk Tetrahedron

Abstract: Sun tracker dua sumbu berbentuk geometri tetrahedron yang sudah dikembangkan memiliki tingkat persentase error akurasi sebesar 31,26% dan kecepatan 0,063 m/s. Nilai akurasi dan kecepatan tersebut masih rendah untuk melacak cahaya matahari pada kondisi ruang terbuka. Penelitian ini bertujuan untuk memperbaiki tingkat akurasi dan sun tracker tetrahedron tersebut. Metode yang digunakan untuk memperoleh ketepatan pelacakan adalah dengan menerapkan sistem pengontrol yang membentuk sistem pelacak menggunakan kendali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
3
0
1
Order By: Relevance
“…Penelitian mengenai penjejak cahaya telah ada sebelumnya menggunakan algoritma PID [1]. Fokus penelitian tersebut adalah mengkaji tingkat ketepatan dan kecepatan penjejak cahaya untuk meningkatkan pemanfaatan energi yang dihasilkan oleh panel surya.…”
Section: Pendahuluanunclassified
“…Penelitian mengenai penjejak cahaya telah ada sebelumnya menggunakan algoritma PID [1]. Fokus penelitian tersebut adalah mengkaji tingkat ketepatan dan kecepatan penjejak cahaya untuk meningkatkan pemanfaatan energi yang dihasilkan oleh panel surya.…”
Section: Pendahuluanunclassified
“…The PD control system has a low level of precision, while the PID control system has a low level of accuracy. Studies [4] and [28] are previous studies that also investigated the sensor-based tetrahedron. However, this study uses different sensor designs and mechanisms.…”
Section: Analysis Of Accuracy and Precisionmentioning
confidence: 99%
“…This proves that the P control system in this study is better than the previous study. Then in the study [28], which also uses a PID control system, the MAE value is 0.65 on the X-axis and 0.54 on the Y-axis. Comparison with the P control system obtains a smaller X-axis value and a larger Y-axis value.…”
Section: Analysis Of Accuracy and Precisionmentioning
confidence: 99%
“…Research using a PID controller [10] whose results showed the solar tracker accuracy was ±0.5°, and produced 26.9% and 12.8% higher power than a fixed PV system. Researchers [24] used a PID controller, with the results of the study showing an accuracy error percentage rate of 31.26% and a speed of 0.063 m/s. Researchers using the ANFIS algorithm [25] proved that ANFIS can be used adequately to design and implement sun tracking systems.…”
Section: Introductionmentioning
confidence: 99%